استخدام التعليم الإلكتروني لتدريس القرآن الكريم بجامعة القرآن الكريم والعلوم الإسلامية من وجهة نظر المختصين والممارسين - عبدالمجيد، طه محمد سعيد Abdulmajid, Taha Mohammed Said; عبدالمجيد، ياسر محمد سعيد; عمر، محمد الشيخ (جامعة أم درمان الإسلامية - معهد البحوث والدراسات الإستراتيجية, 2016)
هدفت الدراسة إلى تحديد أهمية مطالب استخدام التعليم الإلكتروني ودرجة توافرها في كل من (برنامج القرآن الكريم بالجامعة، معلم القرآن، البيئة التعليمية) من وجهة نظر المختصين. استخدم الباحثون المنهج الوصفي التحليلي وتكون مجتمع الدراسة من المختصين وهم معلمو القرآن الكريم حيث بلغ عددهم (42) من أعضاء هيئة التدريس بجامعة القرآن الكريم والعلوم الإسلامية -كلية القرآن.. أما عينة الدراسة فقام الباحثين باختيار كل مجتمع الدراسة بجامعة القرآن الكريم. أغلب المبحوثين لا يستخدمون وسائل التعليم الإلكتروني كما أكدت الدراسة أن جميع المطالب اللازم توافرها في المنهج وعضو هيئة التدريس والبيئة التعليمية لاستخدام التعليم الإلكتروني. مهمة. وأوصت الدراسة بالاستفادة من المطالب التي حددتها الدراسة، الاستفادة من المطالب التي حددتها الدراسة في بناء المنهج الإلكتروني المتكامل لتعليم القرآن The study aimed to determine the demands of the use of electronic learning required in each of the (The holly Quran programme of university) from the viewpoint of specialists and to identify the degree of importance and availability demands the use of e-learning in each of the (curriculum Koran, teacher Koran) From the perspective of practitioners. The researchers used the descriptive method and analytical study population consisted of specialists who are gurus Koran where numbered (42) of the University faculty members Koran and Islamic Sciences - College of the Holy. And fourth year students of the Faculty of Education in the Holy Quran and Islamic Studies University of the Holy Quran and Islamic sciences. The study sample so the researchers choose every community of the study at the University of the Holy Quran Results: the most important results of the following: the majority of the respondents were of the used means of e-learning, where the percentage as study confirmed that all the demands required in the curriculum and the faculty member and the learning environment for the use of e-learning. Important. Recommendations: the construction of electronic curriculum to teach the Quran
Keywords: المؤسسات الجامعية -- التعليم الإلكتروني -- العلوم الإسلامية -- تعلم القرآن الكريم -- الهيئة التدريسية